How Social Media Improves Students' Speaking Performance: Exploring Self-Regulated English Learning Platform on YouTube.: English - Devita wahdani; Bambang Panca Syahputra (Journal of English Development, 2024)
study aims to investigate students' perceptions of YouTube on their speaking performance. The survey was used as a r This esearch methodology and qualitative approach to conduct a comprehensive and detailed investigation regarding the use of social media in students' speaking processes. This research involved 20 students registered in the English education study program at Muhammadiyah University, North Sumatra. The survey was designed using Google forms and then distributed via WhatsApp groups. Observable behavior and written or verbal statements from individuals provide descriptive data (Moleong, 2004). The themes raised are how speaking skills improve after using social media, preferences for social media for learning to speak, advantages and disadvantages of using social media for learning to speak. Research findings can be concluded from research findings on how students view the use of YouTube in speaking sessions. In the opinion of some students, networking is the main issue in using YouTube for academic purposes. Students can improve their speaking skills, especially those related to vocabulary and pronunciation, by watching YouTube.